Educational Supervision as Internal Quality Assurance Mechanism: Conceptualizing the Quality Assurance-Based Supervision Cycle (QASC) for Quality Education (SDG 4) - Hilmi Qosim Mubah; Yatim Riyanto; Erny Roesminingsih (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To examines how educational supervision functions as an organizational quality assurance mechanism within the Internal Quality Assurance (IQA) system and develops a conceptual framework explaining how supervision contributes to sustainable educational quality beyond improving teacher performance. Method: Employed a qualitative case study at MTsN 1 Pamekasan, Indonesia, to explore educational supervision within the Internal Quality Assurance system. Data were gathered between September 2025 and June 2026 through semi-structured interviews with 11 informants. Classroom observations and institutional documents were used to enrich the interview data. The analysis followed the interactive approach of Miles, Huberman, and Saldaña, while the credibility of the findings was strengthened through source triangulation, method triangulation, member checking, peer debriefing, and a comprehensive audit trail. Results: To identified that shape quality-oriented educational supervision: evidence-based supervision planning, collaborative supervision practices, organizational learning, and continuous quality improvement. These processes demonstrate that supervision extends beyond monitoring classroom instruction by generating organizational evidence that supports professional learning, institutional decision making, policy refinement, and the ongoing implementation of Internal Quality Assurance. Novelty: The principal contribution of this study is the development of the Quality Assurance-Based Supervision Cycle (QASC), a conceptual framework explaining how educational supervision, organizational learning, and Internal Quality Assurance operate as an integrated and continuous cycle. The framework offers a broader perspective by positioning educational supervision not merely as a strategy for improving teachers' instructional practices, but as an evidence-informed organizational governance mechanism that drives sustainable educational quality improvement.